The new age of innovation : driving cocreated value through global networks - Prahalad, C. K. (McGraw Hill professional., 2008)
"The New Age of Innovation reveals that the key to creating value and the future growth of every business depends on accessing a global network of resources to co-create unique experiences with customers, one at a time. To achieve this, CEOs, executives, and managers at every level must transform their business processes, technical systems, and supply chain management, implementing key social and technological architecture requirements to create an ongoing innovation advantage. This book explains how to accomplish this shift - one where IT and the management architecture form the corporation's fundamental foundation."--Jacket